Synthesis, and Anti-Tumor Evaluation of Some New Flurbiprofen Derivatives Against MCF-7 and WRL-68 Cell Lines - Kasim S. Hmood; Ammar A. Razzak Mahmood Kubba; Redha I Al-bayati; Abdulrahman M. Saleh (Universitas Gadjah Mada, 2021)
A new series of flurbiprofen derivatives containing thiosemicarbazide moiety (3-7)  was  synthesized from flurbiprofen as parent nucleus by  esterification, hydrazide formation, and  heating with different  aryl isothiocyanate substituents, respectively. Flurbiprofen was also treated with thiosemicarbazide in the  presence POCl3 as  a catalyst,   to produce 1,3,4 -thiadiazole -2-amine (8). Treatment of (8) with different aryl isothiocyanates  produced thiourea derivatives (9-12).  Also, the reaction of  (8)  with different benzoyl chloride substituents produced benzamide compounds (13-15). Eventually , treatment of (8)  with  ethyl acetoacetate(EAA) produced [1,3,4]thiadiazolo[3,2-a]pyrimidin-7-one (16) .The new compounds were  characterized by spectroscopic techniques :FTIR,  1HNMR, and CHNS analysis. A molecular docking  study for  the  synthesized compounds (3-16), against the Vascular Endothelial Growth Factor receptor (VEGFR-2) was applied   and  it  indicated  that compounds 4,7,13, and 15,exhibited the optimum binding energy of     -6.77, -6.12,-6.68, and -6.43 kcal/mol, respectively. Target compounds were  also assessed  for their  in vitro anticancer effects  in a cell-line study. All  of the compounds tested  showed  the most plausible anticancer activity, compared to a positive control(Sorafenib), using in vitro  MTT cytotoxic assay ,against human breast tumor (MCF-7), and normal WRL-68 cell line. The in vitro results revealed that compounds 4,5,10,11,13, and 15 exhibited the highest inhibitory activity at their IC50 concentrations, against MCF-7 cell lines, as follows (122.7,113.9,95,7. 109.1,40.32 and 112.29µg/mL, respectively. While their cytotoxic effect against normal WRL-68 cell line at  their IC50 concentrations, as follow 210.2, 181.3 ,151.7,278.7,80.28, and 236 µg/mL, respectively, therefore,  such compounds were considered more selective toward MCF-7 than normal WRL-68,and their selectivity index (SI): 1.71,1.59,1.59 ,2.55 ,1.99 , and 2.10,respectively . Among the synthesized compounds, the compound 15 was chosen to screen its effect in vitro through multi-parameter cytotoxic assay against MCF-7 breast cancer implemented in High Content Screening (ArrayScan XTI, Thermo Scientific),which  could be taken in consideration as a starting point for the  development  of new anticancer drugs